Fracture development around wellbore excavation: Insights from a 2D thermo-mechanical FDEM analysis - Cui, Wenjun; Liu, Quansheng; Wu, Zhijun; Xu, Xiangyu (Engineering fracture mechanics, 2024)
•A novel thermo-mechanical coupling scheme is developed based on the combined finite-discrete element method (FDEM) to capture the mechanical response of the rock to the isotropic/anisotropic thermal conduction process.•The mechanisms of the creation and development of the excavation damaged zone (EDZ) around the wellbore subject to excavation unloading, drilling mud support, and thermal change in the surrounding rock are analyzed.•The influences of the thermal-mechanical properties of the rock mass, such as the isotropic/anisotropic rock strength and thermal conductivity, thermal expansivity, as well as drilling mud-rock thermal interaction process, on the EDZ development, are discussed. Insights into fracture development and excavation damaged zone (EDZ) formation around wellbore excavation sites are essential for understanding wellbore stability. In this study, a novel thermo-mechanical scheme is implemented in the 2D combined finite-discrete element method (FDEM) to investigate the fracturing process around a wellbore in a high-temperature subsurface environment. The developed scheme captures the isotropic/anisotropic thermal conduction characteristics within the rock formation. The coupled scheme and stress distributions around the wellbore subject to in-situ stress, drilling mud pressure, and temperature changes are validated by closed-form solutions. Fracture development and progressive EDZ formation by various mechanisms are analyzed. The results show that for an unsupported wellbore, fractures initiate in the region of the most severe stress concentration due to excavation unloading and constitute an EDZ that resembles the logarithmic-spiral rupture zone captured by experimental observations and Mohr-Coulomb models, resulting in potential water inrush due to the significantly increased fracture transmissivity of the EDZ and wellbore collapse. The shape and extent of the EDZ for wellbore excavation in the layered rock mass are dominated by the stress redistribution and the presence of low-strength bedding planes favorably oriented for bedding slippage. The excavation unloading-induced stresses can be effectively counteracted by properly applying drilling mud pressure, and the disturbance of the stress field occurs only within a small region, greatly reducing the extension of the EDZ. Thermal contraction of the surrounding rock due to its convective interaction with the cold drilling mud induces extra fractures around the wellbore. The extension of the EDZ is greater with increased thermal expansivity of the rock formation. Overall, the results indicate that the adopted thermo-mechanical FDEM simulation can provide unique geomechanical insight into wellbore stability behavior analysis, in which explicit consideration of the fracturing and fragmentation processes is of great significance.